Genome-enabled phylogenetic and functional reconstruction of an araphid pennate diatom Plagiostriata sp. CCMP470, previously assigned as a radial centric diatom, and its bacterial commensal - Sato, Shinya; Nanjappa, Deepak; Dorrell, Richard G; Vieira, Fabio Rocha Jimenez; Kazamia, Elena; Tirichine, Leila; Veluchamy, Alaguraj; Heilig, Roland; Aury, Jean-Marc; Jaillon, Olivier; Wincker, Patrick; Fussy, Zoltan; et al. (Scientific reports, 2020)
Diatoms are an ecologically fundamental and highly diverse group of algae, dominating marine primary production in both open-water and coastal communities. The diatoms include both centric species, which may have radial or polar symmetry, and the pennates, which include raphid and araphid species and arose within the centric lineage. Here, we use combined microscopic and molecular information to reclassify a diatom strain CCMP470, previously annotated as a radial centric species related to Leptocylindrus danicus, as an araphid pennate species in the staurosiroid lineage, within the genus Plagiostriata. CCMP470 shares key ultrastructural features with Plagiostriata taxa, such as the presence of a sternum with parallel striae, and the presence of a highly reduced labiate process on its valve; and this evolutionary position is robustly supported by multigene phylogenetic analysis. We additionally present a draft genome of CCMP470, which is the first genome available for a staurosiroid lineage. 270 Pfams (19%) found in the CCMP470 genome are not known in other diatom genomes, which otherwise does not hold big novelties compared to genomes of non-staurosiroid diatoms. Notably, our DNA library contains the genome of a bacterium within the Rhodobacterales, an alpha-proteobacterial lineage known frequently to associate with algae. We demonstrate the presence of commensal alpha-proteobacterial sequences in other published algal genome and transcriptome datasets, which may indicate widespread and persistent co-occurrence.
Keywords: Diatoms; Genome; transkriptom; Phylogeny; biologická evoluce; Biological Evolution; Transcriptome; fylogeneze; genom; rozsivky; Gene Expression Profiling; Evolution, Molecular; molekulární evoluce; stanovení celkové genové exprese